2019
DOI: 10.1016/j.ebiom.2019.07.058
|View full text |Cite
|
Sign up to set email alerts
|

Hepatectomy promotes recurrence of liver cancer by enhancing IL-11-STAT3 signaling

Abstract: Background Patients undergoing surgical resection of hepatocellular carcinoma (HCC) are at risk of recurrence; however, the underlying mechanism remains poorly understood. Methods Through the analysis of gene expression profiles in tumour and matched normal tissues from patients with hepatocellular carcinoma (HCC), we identified differences in interleukin-11 ( IL-11 ) expression. Further, we used genetic mouse, orthotopic tumour, chemically in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
68
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(71 citation statements)
references
References 47 publications
0
68
0
Order By: Relevance
“…Collectively, this study demonstrates that drug combinations with napabucasin are a viable treatment approach with potential survival benefits and hence a Phase III trial is ongoing for this combination in gastric and gastroesophageal junction cancers (NCT02178956) [98]. In preclinical studies of HCC, napabucasin promoted apoptosis in vitro and suppressed tumor growth in orthotopic mouse models [104]. Using another orthotopic HCC resection mouse model, napabucasin treatment was also observed to decrease the incidence of recurrence after surgery (hepatectomy), which is likely mediated by inhibition of the IL-11/STAT3 signaling axis [104].…”
Section: Targeting Stat3mentioning
confidence: 88%
See 1 more Smart Citation
“…Collectively, this study demonstrates that drug combinations with napabucasin are a viable treatment approach with potential survival benefits and hence a Phase III trial is ongoing for this combination in gastric and gastroesophageal junction cancers (NCT02178956) [98]. In preclinical studies of HCC, napabucasin promoted apoptosis in vitro and suppressed tumor growth in orthotopic mouse models [104]. Using another orthotopic HCC resection mouse model, napabucasin treatment was also observed to decrease the incidence of recurrence after surgery (hepatectomy), which is likely mediated by inhibition of the IL-11/STAT3 signaling axis [104].…”
Section: Targeting Stat3mentioning
confidence: 88%
“…In preclinical studies of HCC, napabucasin promoted apoptosis in vitro and suppressed tumor growth in orthotopic mouse models [104]. Using another orthotopic HCC resection mouse model, napabucasin treatment was also observed to decrease the incidence of recurrence after surgery (hepatectomy), which is likely mediated by inhibition of the IL-11/STAT3 signaling axis [104]. In addition, AFP and proliferating cell nuclear antigen levels were also reduced after treatment with napabucasin.…”
Section: Targeting Stat3mentioning
confidence: 99%
“…Hu et al indicated that IL-17 promotes the proliferation of liver cancer cells (HBV + ) by activating the IL-6/STAT3 signaling pathway (Hu et al, 2017), and Tian et al found that IL-17 expression and promoter methylation were closely related to the progression of chronic HBV infection, particularly in patients with HCC (Tian et al, 2019). Moreover, Wang et al revealed that the IL-11 has a chief role in postsurgical HCC recurrence; they also found that the IL-11/STAT3 signaling pathway promotes the proliferation of tumor cells and that the inhibition of IL-11/STAT3 signaling could reduce the postsurgical recurrence of HCC (Wang et al, 2019). IL-11 regulates a variety of immune cells to participate in the immune response.…”
Section: Discussionmentioning
confidence: 99%
“…organs. 38,39 Recent studies have also suggested its role in osteosarcoma deterioration, 40 postoperative recurrence of liver cancer 41,42 and migration and survival of gastric cancer cells. 43 Based on the current knowledge of the biological properties of IL-11 and its role in cancer, IL-11 signaling inhibition might be a new therapeutic approach for cancer treatment.…”
Section: Discussionmentioning
confidence: 99%